2011
DOI: 10.1130/g31825.1
|View full text |Cite
|
Sign up to set email alerts
|

Northeastern Atlantic cold-water coral reefs and climate

Abstract: U-series age patterns obtained on reef framework-forming cold-water corals collected over a nearly 6,000 km long continental margin sector, extending from off Mauritania to the south-western Barents Sea reveal strong climate influences on the geographical distribution and sustained development of these ecosystems. During glacial times densely populated cold-water coral reefs flourished in the temperate east Atlantic, where at present only scarce live coral occurrences exist. In contrast, climate warming induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 26 publications
(28 reference statements)
2
99
2
Order By: Relevance
“…The last 11 ka, as well as previous warm interglacial periods such as marine isotope stages (MIS) 5, 7 and 9, have been favourable for coral growth and thus coral carbonate mound development in the NE Atlantic between 50°N and 70°N (Frank et al, 2009;Douville et al, 2010;. To date no Lophelia from glacial periods have been found at these latitudes in the NE Atlantic (Dorschel, 2003;Kenyon et al, 2003;Schröder-Ritzrau et al, 2003;Frank et al, 2004;Dorschel et al, 2007;Rüggeberg et al, 2007;Mienis et al, 2009), hence glacial conditions are assumed to be detrimental to the growth of individual coral colonies and thus to coral carbonate mounds at these latitudes (Kenyon et al, 2003;Frank et al, 2009;Frank et al, 2011). U-series dating of cold-water coral fragments from coral carbonate mounds on the European continental margin allows quantification of the vertical mound growth rate (VMGR), a method that reveals periods of mound build-up coupled to palaeoceanographic changes (Frank et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last 11 ka, as well as previous warm interglacial periods such as marine isotope stages (MIS) 5, 7 and 9, have been favourable for coral growth and thus coral carbonate mound development in the NE Atlantic between 50°N and 70°N (Frank et al, 2009;Douville et al, 2010;. To date no Lophelia from glacial periods have been found at these latitudes in the NE Atlantic (Dorschel, 2003;Kenyon et al, 2003;Schröder-Ritzrau et al, 2003;Frank et al, 2004;Dorschel et al, 2007;Rüggeberg et al, 2007;Mienis et al, 2009), hence glacial conditions are assumed to be detrimental to the growth of individual coral colonies and thus to coral carbonate mounds at these latitudes (Kenyon et al, 2003;Frank et al, 2009;Frank et al, 2011). U-series dating of cold-water coral fragments from coral carbonate mounds on the European continental margin allows quantification of the vertical mound growth rate (VMGR), a method that reveals periods of mound build-up coupled to palaeoceanographic changes (Frank et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because coral framework acts as a sediment trap for both laterally and vertically advected sediment flux, the VMGR is consistently higher during conditions favourable for coral growth. Such conditions are met when local hydrodynamics facilitate repeated coral recruitment events that form eventually coalesce to form large reef frameworks (Genin et al, 1986;Frederiksen et al, 1992;White et al, 2005;Mienis et al, 2007;White, 2007;Davies et al, 2009;Mienis et al, 2009;Frank et al, 2009;Frank et al, 2011; Douarin et al, in review; Henry et al, submitted).Since cold-water coral mounds and continental shelves are both frequently characterized by high growth and sedimentation rates, it is assumed that shallow inner-shelf cold-water coral reefs may have especially high growth rates. Sediment cores through these structures could therefore offer the potential for high-resolution Because the cores contained coral fragments embedded in sediment they were frozen prior to splitting to avoid disrupting the position and orientation of the coral fragments and to preserve the core's internal sedimentary structure.…”
mentioning
confidence: 99%
“…Their complex branching and anastomizing complex colonies have proved difficult for sclerochronology (Risk et al, 2005). However, the occurrence of these species is strongly influenced by climate (Rüggeberg et al, 2008;Frank et al, 2009Frank et al, , 2011 and their skeletons can be used to reconstruct water mass provenance Copard et al, 2010Copard et al, , 2011. For both species, independent growth rate estimates have been obtained from in situ observations and aquarium studies.…”
Section: P Sabatier Et Al: Rapid Growth Rate Of Madrepora Oculata Amentioning
confidence: 99%
“…However, recent studies have shown that these unique ecosystems of the North Atlantic have been sensitive to other environmental changes such as bottom currents and nutrient availability (e.g. Frank et al, 2011;Kano et al, 2007;Rüggeberg et al, 2007;Raddatz et al, 2011Raddatz et al, , 2014. Importantly, more than 95 % of living CWC reefs in the modern ocean occur above the aragonite saturation horizon (ASH) indicating that a lower seawater pH jeopardizes their existence (Guinotte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%